Mengulik Peran Istri Gembala dalam Menyokong Pelayanan Suami di Gereja Beraliran Pentakostal - Yolanda Arista Wibowo; Ruwi Hastuti; Sukarno Hadi (Sekolah Tinggi Teologi Nusantara, 2024)
Pastoral ministry in Pentecostal churches is often viewed as the primary responsibility of a congregational pastor. However, the wife's contribution in supporting her husband's pastoral ministry also plays an important role that has not been widely studied. The problem that is attempted to be studied in this research is related to the tendency that the pastor's wife is not considered to have a role in pastoral ministry. This article aims to examine the role of wives in supporting their husbands' ministry in the Pentecostal church both theologically and in ministry practice. This research uses a qualitative-descriptive method with a literature review approach.. In conclusion, wives have a central role in supporting their husband's ministry through spiritual support, emotional support, practical support, and being a role model. Apart from that, through various things, the pastor's wife is able to have a significant impact in terms of maintaining the balance of her husband's ministry in the pastoral realm and family responsibilities. AbstrakPelayanan pastoral di gereja Pentakostal sering kali dipandang sebagai tanggung jawab utama seorang gembala jemaat. Namun, kontribusi istri dalam mendukung pelayanan pastoral suami juga memainkan peran penting yang belum banyak diteliti. Masalah yang coba dikaji dalam penelitian ini terkait adanya kecenderungan istri gembala yang tidak dianggap peranannya dalam pelayanan pastoral. Artikel ini bermaksud untuk mengkaji peran istri dalam mendukung pelayanan suami di gereja Pentakostal baik secara teologis maupun praktik pelayanan. Penelitian ini menggunakan metode kualitatif-deskriptif dengan pendekatan kajian literatur. Disimpulkan, istri memiliki peran sentral dalam menyokong pelayanan suami melalui dukungan spritual, dukungan emosional, dukungan praktis, serta menjadi role model. Selain itu, melalui berbagai perannya, istri gembala mampu memberi dampak yang signifikan juga dalam hal menjaga keseimbangan pelayanan suami di ranah pastoral dan tanggung jawab keluarga. Kata Kunci: Gereja Pentakostal; Istri Gembala; Pelayanan Pastoral.